2002
DOI: 10.1103/physrevlett.89.175003
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Double-Layer Target for the Generation of High-Quality Laser-Accelerated Ion Beams

Abstract: In order to achieve a high-quality, i.e., monoenergetic, intense ion beam, we propose the use of a double-layer target. The first layer, at the target front, consists of high-Z atoms, while the second (rear) layer is a thin coating of low-Z atoms. The generation of high-quality proton beams from the double-layer target, irradiated by an ultraintense laser pulse, is demonstrated with three-dimensional particle-in-cell simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(104 citation statements)
references
References 28 publications
1
103
0
Order By: Relevance
“…In this paper we study the interaction of a super-intense, ultra-clean, ulta-short, tightly The usual scenario of ion acceleration often discussed in both the experimental [1][2][3] and the PIC simulation [5,6,[24][25][26][27][28][29] literature, is acceleration by the sheath of hot electrons generated by the high-intensity laser pulse at the front of the target. As the laser heats and accelerates these electrons they propagate through the entire target.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we study the interaction of a super-intense, ultra-clean, ulta-short, tightly The usual scenario of ion acceleration often discussed in both the experimental [1][2][3] and the PIC simulation [5,6,[24][25][26][27][28][29] literature, is acceleration by the sheath of hot electrons generated by the high-intensity laser pulse at the front of the target. As the laser heats and accelerates these electrons they propagate through the entire target.…”
Section: Introductionmentioning
confidence: 99%
“…Schwoerer and his team produced quasi-monoenergetic protons by irradiating microstructured targets, an idea that had been suggested by Esirkepov et al in 2002, [50]. The authors pointed out that the resulting proton spectrum has a strong correlation to the spatial distribution of the protons on the target surface as shown in Figure 9a.…”
Section: Figurementioning
confidence: 99%
“…By using particle-in-cell (PIC) simulations, Liu et al showed that energetic collimated ion bunches can be achieved with a thin concave target [9]. A micro-structured double layer target was proposed for the generation of high-quality ion beams [10]. Cowan et al successfully demonstrated a laser virtual-cathode method to get an ultralow-emittance energetic proton beam [11].…”
Section: Introductionmentioning
confidence: 99%